Euro-Par 2011 Parallel Processing 17th International Conference, Euro-Par 2011, Bordeaux, France, August 29 - September 2, 2011, Proceedings, Part II - Jeannot, Emmanuel; Namyst, Raymond; Roman, Jean.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two-volume set LNCS 6852/6853 constitutes the refereed proceedings of the 17th International Euro-Par Conference held in Bordeaux, France, in August/September 2011. The 81 revised full papers presented were carefully reviewed and selected from 271 submissions. The papers are organized in topical sections on support tools and environments; performance prediction and evaluation; scheduling and load-balancing; high-performance architectures and compilers; parallel and distributed data management; grid, cluster and cloud computing; peer to peer computing; distributed systems and algorithms; parallel and distributed programming; parallel numerical algorithms; multicore and manycore programming; theory and algorithms for parallel computation; high performance networks and mobile ubiquitous computing.
Keywords: Computer science; Software engineering; Operating systems (Computers).; Electronic data processing; Computer Science; Computation by Abstract Devices; Programming Techniques; Programming Languages, Compilers, Interpreters; Numeric Computing; Special Purpose and Application-Based Systems; Operating Systems